Natural Babesia bovis Infection in Water Buffaloes (Bubalus bubalis) and Crossbred Cattle under Field Conditions in Egypt: a Preliminary Study. - Yasser Mahmmod (Tehran University of Medical Sciences, 2014)
Background: There is a little or no data available on the natural Babesia bovis (B. bovis) infection in water buffaloes(Bubalus bubalis) comparing to the available one for cattle. This study was conducted to investigate the natural B. bovis infection in water buffaloes in comparison to crossbred cattle under field conditions in Egypt. Methods: A total of 35 buffaloes and cattle were clinically and laboratory investigated from March to June 2008. Twenty-nine buffaloes and cattle out of 35 were naturally infected with B. bovis and showed signs of bovine babesiosis. Three cows and three buffaloes showed no clinical signs and were free from external, internal, and blood parasites served as control group. Results: Babesia bovis-infected cattle showed typical signs of bovine babesiosis while B. bovis-infected buffaloes showed a milder form (less severe) of the clinical signs. Advanced cases of cattle showed dark brown to dark red (coffee-color) urine, hemoglobinuria and nervous manifestations while these manifestations were not detected in the infected buffaloes. Hematological changes in both species however, these changes were less significant in buffaloes than those reported in cattle. Conclusion: This paper documents the first description of natural B. bovis infection in water buffaloes which were found to be more likely to be tolerant than cattle to the natural clinical infection with B. bovis and its subsequent haematological changes. Our finding may lead to a better understanding of the disease pattern of B. bovis infection under field conditions in buffaloes.